The economics of land degradation: Toward an integrated global assessment - Nkonya, Ephraim M.; Gerber, Nicolas; Baumgartner, Philipp; von Braun, Joachim; De Pinto, Alessandro; Graw, Valerie; Kato, Edward; Kloos, Julia; Walter, Teresa (Peter Lang GmbH, 2011)
Land degradation is increasingly considered as a global problem. The extent of degraded and degrading areas adversely impacts on large numbers of people and leads to significant social and economic costs, thus raising the questions: In which way is it worth taking action against land degradation? Where and when should action take place, and what are costs related to certain actions? For policy makers it is important to know the social and economic costs linked to the current and future status of land degradation. A conceptual framework that allows comparing the costs of action against land degradation versus the costs of inaction is provided in this book. The applicability of the framework is illustrated with case studies and prepares the ground for a global assessment on the costs of land degradation.